The Development of Painting in the Dutch East Indies in 1800-1936 - Shela Dwi Utari; Daya Negri Wijaya (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The development of art in the Dutch East Indies was very dynamic by what was the tendency of the school at that time. Before the influence of European culture entered the painting, Indonesian people had characteristics related to traditional painting. However, when the European genre of painting entered, it triggered the development of indies painting and indie mooi. Therefore, this article wants to examine the development of painting in the Dutch East Indies from 1800-1936. The method used is a literature study by reviewing journals, books, or historical sources that are contemporary or related to painting from 1800-1936. The results of this article found that before 1800, traditional painters used puppet media as a painting medium. Then the story's focus is the Heroic Stories, and the religious aspect takes precedence. However, when colonial penetration entered the painting, it was secular and more commercial according to market interests like mooi indie and indis. The Pita Maha in Bali is evidence of the acculturation of European and traditional painting to this day.